Sistem pengendalian internal, kinerja karyawan, dan kinerja perusahaan - Jerry, Jerry; Hadianto, Bram (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This study aims to prove the impact of employee achievement (EA) and an internal control system (ICS) on company performance (CP). Besides, verifying the influence of the ICS on EA and the mediation effect of EA on the association between ICS and CP become the other purposes. This study utilizes 120 employees from 15 general insurance companies in Bandung as the sample by snowball sampling technique and covariance-based structural equation model (CBSEM) to analyze the responses to the questionnaire. Because of the responses, this study tests their validity and reliability. After achieving them, this study detects and finds the response fitness with the CBSEM. Based on the hypothesis testing, this study demonstrates three evidence. Firstly, EA and ICS have a positive tendency towards CP. Secondly, a positive association between ICS and EA occurs. Finally, the mediating effect of EA on the relationship between ICS and CP exists. Considering these research results, ICS is the primary driver; therefore, general insurance companies must focus on five aspects: (1) environmental control, (2) risk valuation, (3) controlling the action, (4) information and communication, and (5) monitoring action, to make employees perform, causing the company to attain its goals.